Applied numerical analysis - Gerald, Curtis F. (Addison-Wesley, 1999)
Numerical computing and computers. Solving nonlinear equations. Solving sets of equations. Interpolation and curve fitting. Approximation of functions. Numerical differentiation and numerical integration. Numerical solution of ordinary differential equations...